The church and genetically modified food in Nigeria: An ethical appraisal - Ekeke Emeka C. (Bangladesh Journal of Bioethics, 2021)
The church in Nigeria does not seem to know the trend in food production where genetically modified food has taken hold of global agriculture. Pastors and Priests seem blank on what is happening, either because of ignorance, carelessness, or due to lack of biblical basis on which to teach or formulate policy. Despite these, the Christian populace in Nigeria is not left out in the onslaught of genetically modified organisms and foods as they continue to consume these products. This paper ethically appraises the role of the church in raising awareness and educating her adherents on the issues surrounding genetically modified food in Nigeria. Following qualitative and Christian ethical approaches, the paper argues that Christian churches in Nigeria should establish a committee that will study and advise them on the harmless foods for consumption in Nigeria.